DOI: 10.14264/uql.2019.862
|View full text |Cite
|
Sign up to set email alerts
|

Selection strategies to improve yield in macadamia using component traits and genomics

Abstract: Macadamias (Macadamia integrifolia, M. tetraphylla, and their hybrids) are native to the east coast of Australia, and are grown commercially around the world for their high quality edible nut kernel. Breeding new cultivars for high nut yield is a lengthy and laborious process that can take over two decades. Evaluations are time-consuming due to the long juvenile period of four or more years, and the low correlation between young and mature tree yield means that at least eight years of evaluations are required.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 186 publications
(494 reference statements)
0
8
0
Order By: Relevance
“…Based on Model 1, the variance component analysis revealed that genetic factors played a key role in the variation of traits of this study. The broad-sense heritability for tree height (0.60), trunk circumference (0.54), and canopy width (0.51) were higher than reported in previous studies of cultivars and breeding progeny [36,37,40]. This may partly be due to the inflation of genetic variance due to the evaluation of accessions from multiple species which differ in average performance.…”
Section: Variation In Growth and Nut Traitsmentioning
confidence: 65%
See 1 more Smart Citation
“…Based on Model 1, the variance component analysis revealed that genetic factors played a key role in the variation of traits of this study. The broad-sense heritability for tree height (0.60), trunk circumference (0.54), and canopy width (0.51) were higher than reported in previous studies of cultivars and breeding progeny [36,37,40]. This may partly be due to the inflation of genetic variance due to the evaluation of accessions from multiple species which differ in average performance.…”
Section: Variation In Growth and Nut Traitsmentioning
confidence: 65%
“…These results suggested that the genetic improvement for nut size could contribute to the profitability of the growers and processors by increasing kernel yield. In another study on mature age breeding progeny, O'Connor [40] identified a strong genetic correlation between individual nut weight and nut-in-shell yield (r = 0.40) and indicated that larger nuts can be a major genetic determinant of increased yield. Nut weight also correlated positively with shell weight (0.95) and correlated negatively with kernel recovery (−0.28).…”
Section: Correlations Among Phenotypic Traitsmentioning
confidence: 99%
“…The implementation of GS in macadamia may include prediction and deployment across environments. The current study population had limited replication of genotypes across environments and did not include G x E interactions in prediction models as preliminary results found no evidence of G x E in this experimental material [48]. Previous studies have found some evidence that G x E may affect macadamia yield [5,12].…”
Section: Comparison Of Prediction Models and Cross-validation Methodsmentioning
confidence: 88%
“…Jia and Jannink [63] found that prediction accuracy was increased for a trait with low heritability by including information for a correlated trait with high heritability. Estimates of heritability and genetic correlations between yield and various component traits have been made [48] and, thus, this information could be used to inform multi-trait GS. Distinctions can also be made between linked QTLs (linkage between multiple QTLs affecting different traits) and pleiotropic QTL (one gene affecting multiple traits), using multi-trait methods, like those employed by Bolormaa, Pryce [64].…”
Section: Future Research Using Gs In Macadamiamentioning
confidence: 99%
See 1 more Smart Citation